Banks' leverage behaviour in a two-agent New Keynesian model - Andrea Boitani; Chiara Punzo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
In a NK model with two types of rational agents, savers and capitalists, and non-maximizing banks, financial shocks do affect the macroeconomic dynamics depending on banks' behaviour as for their leverage ratio. We first show that the level of banks' leverage - which may be imposed by banks regulation - affects the steady state level of output, employment and consumption, as might be expected in a non-Modigliani-Miller world. Different banks' behaviour after a shock has widely different effects on the macroeconomic dynamics: passive leverage results to be shock absorbing and capable of neutralizing an initial financial shock, whilst procyclical behaviour implies higher and more persistent instability and distributive effects than the constant leverage behaviour. Finally, we show that the interaction of procyclical leverage with hysteresis in output and employment stregthens the persistence of financial shocks.
Keywords: E32; E44; E70; G01; 330; Leverage; Procyclicality; Two-agent model; Non-maximising banks